(untitled) (Acta Scientiarum. Biological Sciences, 2025)
Fish and fishing products are among the most traded food types worldwide. Thus, the use of economically viable and sustainable diet supplementation alternatives to ensure animal health improvement is increasingly requested. Furthermore, the adoption of agricultural waste is a sustainable activity that helps reducing environmental pollution. The aim of the present study is to assess the antioxidant effect of a diet based on different rice bran phytic acid (PA) concentrations, namely: 0.5, 1.0, 1.5 and 2.0% by using oxidative stress and detoxification biomarkers in fish species Cyprinus carpio and Rhamdia quelen. The activity of glutathione S-transferase (GST) and hepatic catalase (CAT) in C. carpio decreased at 2.0% PA. Lipid peroxidation (LPO) increased in the liver at 2.0% PA and the carbonylated protein (CP) content decreased at all tested concentrations. The activity of GST increased in R. quelen at 2.0% PA, whereas CAT activity decreased at 0.5 and 1.5% PA. According to the current study, phytic acid might bring benefits to fish at concentrations up to 1.5% PA. In addition, adding this antioxidant to the feeding of fish bred in ponds can even lead to more significant effects.